A New Two-Port MIMO Filtenna With Tunable Bandwidth and Center Frequency - Alper Turkeli; Ali Kursad Gorur; Yasemin Altuncu; Adnan Gorur (IEEE Access)
A new two-port MIMO filtenna with center frequency and bandwidth tunability is introduced by integrating a tunable filter into the feeding section of a monopole antenna. The tunable filter is constructed by a dual-mode square loop resonator having four varactor diodes. One of the varactor diodes are separated from the other varactors, so that the tuning process is achieved by using two different bias voltages. Thus, the bandwidth can be tuned by the singly biased varactor diode, while the center frequency is tuned by controlling all varactors. The monopole antenna is developed by a slotted radiation patch to obtain high gain within the desired frequency band which must also cover the tuning range. A two-port tunable MIMO filtenna was fabricated and successfully tested for experimental validation. The 10-dB bandwidth of the designed MIMO filtenna can be tuned from 340 to 690 MHz at the highest center frequency, while the center frequency is tuned between 3.4 and 3.93 GHz. Within the tuning range, the maximum peak gain varies between 1.6 and 4 dBi in the electromagnetic (EM) simulations. Isolation between the outputs of the MIMO filtenna was measured as better than -20 dB and envelope correlation coefficient (EEC) was observed as less than 0.001. Diversity gain (DG) and mean effective gain (MEG) were obtained as close to 10 and less than 3 dB, respectively. Moreover, radiation efficiency of the proposed MIMO filtenna was obtained between 60% and 72%.